2017
DOI: 10.1080/19476337.2017.1331265
|View full text |Cite
|
Sign up to set email alerts
|

Physical characteristics and nutritional composition of gluten-free bread with share of freeze-dried red potatoes

Abstract: The aim of the study was to compare nutritional composition and physical properties of gluten-free bread samples with a 5% addition of freeze-dried red potatoes (variety: Blue Star, Magenta Love, Violeta), in order to check the suitability for nutritional enrichment of such products. It was observed that the use of potato variety Magenta Love resulted in the most beneficial nutritional quality of gluten-free bread (especially high content of insoluble fibre), and its best physical properties (high volume, low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Total dietary fiber content was larger in the case of Magenta Love (14% more than in Violetta). Taking into account that total dietary fiber in freeze-dried red and purple potatoes ranged between 7 and 8.76 g/100 g, its soluble fraction varied between 1.87 – 2.74 and insoluble fraction 3.9 – 6 g/100 g [ 35 ] it could be concluded that the pulp is much more abundant in fiber ( Table 1 ) than respective freeze-dried tubers [ 35 ]. In the case of total dietary fiber (TDF) the content in pulp is twice as high as in freeze-dried potato tissue, in the case of insoluble dietary fiber (IDF) and soluble dietary fiber (SDF) the increase is 3-4-fold and 1.5-fold, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Total dietary fiber content was larger in the case of Magenta Love (14% more than in Violetta). Taking into account that total dietary fiber in freeze-dried red and purple potatoes ranged between 7 and 8.76 g/100 g, its soluble fraction varied between 1.87 – 2.74 and insoluble fraction 3.9 – 6 g/100 g [ 35 ] it could be concluded that the pulp is much more abundant in fiber ( Table 1 ) than respective freeze-dried tubers [ 35 ]. In the case of total dietary fiber (TDF) the content in pulp is twice as high as in freeze-dried potato tissue, in the case of insoluble dietary fiber (IDF) and soluble dietary fiber (SDF) the increase is 3-4-fold and 1.5-fold, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies carried out image analysis of the cells of the kernels. They identified the following results: (1) that the GFB obtained from a formulation based on unripe banana flour (specific volume = 4.82 cm 3 /g) showed that 0.95% of the cells were large, the number of the large cell was 6.17, whereas the number of the largest cell was 1.47; (2) that the GFP obtained from a formulation based on RF/swett potato flour (PF)/buckwheat flour (BCWF) (specific volume = 4.52 cm 3 /g) showed mean cell area (mm 2 ) equal to 0.339, circularity equal to 0.699 mm and cell density equal to 811, 21; (3) that the GFB obtained from a PS-based formulation added of 12% sodium caseinate (specific volume = 3.56 cm 3 /g) showed porosity equal to 0.409, cell density (1/cm 2 ) equal to 9.0 and % of pores > 5 mm equal to 0.446; (4) that the GFB obtained from a formulation based on MS/potato starch (PS)/red potatoes showed porosity equal to 0.401, number of rotten equal to 1408, number of pores/cm 2 equal to 4779 ( Table 1 ) [ 49 , 73 , 97 , 148 ]. Esteller [ 55 ] found for the porosity of the bread crumb of the commercial loaf, based on wheat flour, an average area of 0.41 mm 2 , half diameter equal to 0.38 mm, and average perimeter equal to 1.37 mm.…”
Section: Discussionmentioning
confidence: 99%
“…There is a number of possibilities for enriching glutenfree bread, ranging from addition of pseudocereals, oilseeds, vegetables, and fruits to the use of by-products manufactured by food processing industry [3][4][5][6][7][8][9][10][11][12]. One of the additives with a high potential for providing a broad range of prohealth substances is fruit pomace.…”
Section: Introductionmentioning
confidence: 99%